Understanding tourism - Medlik, S (Butterworth-Heinemann, 2015)
Understanding Tourism examines tourism in 1000 questions and answers. It is intended for students and teachers of tourism worldwide, those who earn their living through tourism or who simply like being tourists, expecially if they enjoy quizzes. Students need to know what progress they are making, to test and consolidate their knowledge. Teachers need to know their students' progress, any learning problems, what parts of the syllabus are going down well or proving difficult. Both need feedback. Arranged in ten parts, which broadly correspond to most syllabus elements studied in schools, colleges and universities, the wide-ranging repertoire also includes such topics as who was who in tourism in the UK and worldwide; what Prime Ministers thought about tourism; who are UK and world leaders in tourism; UK, US, Australian and Caribbean tourism in figures; US versus UK language; the language of North of the (English) border; creative marketing campaigns and messages. Professor Medlik is an author, consultant and educator with more than 30 years of involvement in tourism. He held several senior academic appointments in Britain and other countries, advised a number of companies, as well as tourism, educational and other organizations, and was the first chairman of the Tourism Society. His published work includes 20 books and other publications and more than 100 contributions to the professional and technical press. 1000 questions and answers Covers wide range of courses Expert panel reviewed questions!